Exploration of the molecular mechanism behind a novel natural genic male-sterile mutation of 1205A in Brassica napus - Lijing Xiao; Jinze Zhang; Shaomin Guo; Hairun Jin; Qingjing Ouyang; Xu Long; Zhongbin Yan; Entang Tian (BMC Plant Biology)
Abstract The use of a male sterility hybrid seed production system has resulted in a significant increase in rapeseed yields by over 20%. Nevertheless, the mechanisms underlying male sterility remain largely unexamined. This study presents a spontaneous recessive genic male-sterile (RGMS) mutant of 1205A, which was employed to establish two two-line hybrid production systems: 1205AB and NT7G132AB. Cytological investigations reveal that the mutation occurs at the early microspore stage, resulting in premature degradation of pollen. Through inheritance analysis, linkage mapping, and bulked-segregant analysis sequencing (BSA-Seq), a single gene locus, designated Bna1205ams1, was identified within the QTL region on chrC03 (15.36–18.90 Mb). The development of three newly co-segregated kompetitive allele-specific PCR (KASP) markers, in conjunction with two traditional co-segregated markers, allowed for the refinement of the QTL of Bna1205ams1 to a segment of 181.47 kb. This refinement facilitated the identification of a candidate gene, BnaC03g27700D, through functional and expression analyses. Furthermore, the subcellular localization of BnaC03g27700D was examined. Metabolic fluctuations associated with the fertility gene were observed, particularly in processes related to aborted tapetal programmed cell death (PCD), which may contribute to reduced pollen fertility with abnormal pollen exine. A strong correlation was also established between BnaC03g27700D and thirteen metabolites. This study not only offers valuable insights into the research and practical application of plant male sterility but also serves as a case study on the genetic regulatory mechanisms governing male sterility.